Development of Leishmania mexicana and Leishmania amazonensis in Lutzomyia evansi (Diptera: Psychodidae, Phlebotomine) - VÍVENES, MARÍA ALEJANDRA; OVIEDO, MILAGROS; MÁRQUEZ, JULIO CÉSAR (Revista Colombiana de Entomología, 2005)
The aim of this paper was to study the morphological changes in the development of Leishmania mexicana (MHOM/VE/72/AZV) and L. amazonensis (IFLA/BR/67/PH8) in Lutzomyia evansi. Females of Lu. evansi fed on a hamster tarsal lesion and were examined for infection at 24 h intervals from 24 h to 168 h post- feeding. The pattern of development of Le. mexicana and Le. amazonensis in Lu. evansi was suprapylarian consistent with what has been described for species of the Le. mexicana complex. Transformation from amastigote to procyclical forms occurred in both species at 24 - 48 h post-infection. The parasites showed their adaptation to the gut environment of Lu. evansi and development to mature forms: nectomonads, haptomonads and paramastigotes. The paramastigote form was observed in low percentage at 120 h post-infected ingestion in both species. The early depletion of nutrients in Lu. evansi, due to a faster rate of digestion (3 to 4 days), could explain the low percentage of development reaching the paramastigote forms and the absence of the metacyclical forms in this model.